Pengaruh RoA, RoE, dan NPM terhadap Harga Saham Perusahaan Sektor Property and Real Estate yang terdaftar di BEI dengan EPS sebagai Variabel Intervening Periode 2019-2021 - Saputra, Danar Wahyu; AC, Ali Mauludi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to determine the effect of Return on Assets, Return on Equity, and Net Profit Margin, on Stock Prices of Property and Real Estate Sector Companies listed on the IDX with Earning Per Share as a Variable Intervening Period 2019-2021. This study uses a quantitative approach to the type of associative research. With the sampling technique using purposive sampling so as to produce 15 companies that are used as research samples. The data analysis technique used in this study uses Panel Data Regression with the help of Eviews 9 Software and also uses path analysis techniques. The results of the study show that partially in equation 1 the ROA and NPM variables have a significant effect on EPS, ROE is not significant on EPS. But ROA has a positive effect on EPS while NPM has a negative effect. Partially the variables ROA, ROE, NPM have no significant effect on stock prices. However, EPS has a significant negative effect on stock prices. Then the results of the path analysis show that ROA and ROE have an effect on stock prices mediated by EPS. However, NPM has no effect on stock prices mediated by EPS. Keywords: ROA; ROE; NPM; EPS; Stock Price